2015
DOI: 10.1002/jsfa.7191
|View full text |Cite
|
Sign up to set email alerts
|

Diversity among mandarin varieties and natural sub‐groups in aroma volatiles compositions

Abstract: Although we found wide differences in aroma-volatiles compositions among varieties belonging to different natural sub-groups, we detected only minor differences among varieties within any natural sub-group. These findings suggest that selecting appropriate parents would enable manipulation of aroma-volatile compositions in future mandarin breeding programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 22 publications
(52 reference statements)
5
11
0
1
Order By: Relevance
“…It was previously observed that mandarin hybrids with a sweet orange genetic background produced more esters and sesquiterpenes, as well as overall aroma volatiles . The present study is in agreement with these conclusions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It was previously observed that mandarin hybrids with a sweet orange genetic background produced more esters and sesquiterpenes, as well as overall aroma volatiles . The present study is in agreement with these conclusions.…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, the Mediterranean ‘Willowleaf’ mandarins produced a relatively low level of limonene and a high level of γ ‐terpinene, whereas ‘Commune’ Clementines had a relatively high level of limonene and a low level of γ ‐terpinene . These observations were supported by a subsequent study reporting that most tangors, tangelos and ‘King’ mandarin also contained relatively low levels of γ ‐terpinene . Our present findings suggest the same conclusion (see Supporting information, Table S6).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding could be useful for apricot geneticists trying to breed new varieties with high antioxidant capacities. Our study also demonstrated that PCA performed on phenolic compounds and antioxidant capacities could be applied to distinguish different apricot varieties and serve as a crucial tool for studying the phenolic compositions among apricot varieties (Goldenberg et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…When fresh fruit is discussed, it is generally accepted that appealing fruit is of attractive size, shape, color and free from blemishes (Putnik and others ). The perceived flavor of mandarins derives from combinations of sensations of taste, aroma and mouth‐feel (Goldenberg and others ). Mediterranean climate and soil will yield mandarins of yellowish‐red color in both peel and segments.…”
Section: Sensory Analysis Of Mandarins and Their Juicesmentioning
confidence: 99%